THE ADDITION OF CALCIUM CARBONATE AND SODIUM CHLORIDE WITH DIFFERENT RATIOS ON THE GROWTH AND SURVIVAL OF VANAME SHRIMP (Litopenaeus vannamei) IN FRESH WATER MEDIA - Muhammad Ridwan; Andre Rachmat Scabra; Zaenal Abidin (Universitas Mataram, 2024)
This research aims to determine the effect of calcium carbonate and sodium chloride on the growth of vannamei shrimp in rearing media with a salinity of 0 ppt. The research was carried out for 45 days, in the Aquaculture Laboratory and Analysis of sodium chloride levels at the Analytical Chemistry Laboratory, Mataram University. using an experimental method with a completely randomized design, consisting of 4 treatments and 3 replications, Using the Completely Randomized Design method. There were 5 treatments with 3 repetitions in each treatment, So in this research there were 15 experimental units. Data were analyzed using Analysis of Variance (ANOVA), and continued with the Duncan test with a confidence level of 95%. The results of the research show the effect of adding calcium carbonate (40 ppm) and Natrium klorida (1,1 ppt) on the growth of vannamei shrimp (Litopenaeus vannamei), namely survival rate, absolute and specific weight growth, absolute and specific length growth, feed conversion ratio, oxygen consumption rate, diversity coefficient, water quality parameters (temperature, dissolved oxygen (Do), Potential of Hydrogen (pH), ammonia, calcium levels, alkalinity and Natrium klorida (NaCl)), is the best treatment for cultivating vannamei shrimp in fresh water media.